An Experimental Study on Submerged AWJ Turning and its Influence on castamide Machining (Comprehensive Journal of Science, 2025)
This study focuses on the application of submerged abrasive water jet turning (AWJT) to enhance the machinability of castamide, a polymer widely used in industrial components. The research investigates the influence of three primary machining parameters—traverse speed (TS), abrasive flow rate (AFR), and spindle speed (SS)—each tested at three levels within a full factorial experimental design. This approach allowed both the independent effects and the interactions of these parameters to be examined comprehensively. To evaluate process performance, two responses were selected: surface roughness (Ra), as an indicator of surface quality, and material removal rate (MRR), representing machining productivity. The collected data were subjected to statistical analysis using analysis of variance (ANOVA) and visualized through three-dimensional surface plots to better illustrate parameter interactions. In addition, multi-criteria decision-making methods, namely TOPSIS and VIKOR, were applied to determine the optimum machining conditions. Regression models were also developed to establish predictive relationships between the process variables and responses. The results demonstrated that submerged AWJT significantly improved machining outcomes compared to conventional AWJT. Specifically, the process reduced noise levels from 108.8 dB to 86.1 dB, improved surface roughness by approximately 15%, and resulted in a slight 5.22% reduction in MRR. ANOVA revealed that traverse speed was the most influential factor, contributing 83.11% to Ra and 85.56% to MRR. Based on the optimization results, the best machining conditions were obtained at TS = 40 mm/min, AFR = 310 g/min, and SS = 300 rpm. These findings highlight the potential of submerged AWJT as an effective and environmentally friendly method for machining castamide and similar materials
Keywords: Submerged turning Abrasive water jet Castamid TOPSIS VIKOR